FAKTOR-FAKTOR NON KEUANGAN YANG MEMPENGARUHI DIKELUARKANNYA OPINI GOING CONCERN - Anggoro Adi Yudhanto; Siti Mutmainah (Diponegoro Journal of Accounting, 2013)
This study aims to examine the influence of auditor reputation, audit tenure, disclosure and opinionshopping to the auditors going concern opinion. Hypothesis (1) auditor reputation positively effect onthe provision by the auditors going concern opinion. (2) audit tenure positively effect on the provisionby the auditors going concern opinion. (3) disclosure positively effect on the provision by the auditorsgoing concern opinion. (4) opinion shopping positively effect on the provision by the auditors goingconcern opinion. Sample of this research used 75 manufacturing companies sample listed onIndonesian Stock Exchange (IDX) between 2008 to 2010. Samples was obtained by purposivesampling. Data were analyzed by logistic regression analysis. The results showed that audit tenure,disclosure and opinion shopping affect the provision by the auditor's going concern opinion. Whereasauditor reputation has no effect on the provision by the auditors going concern opinion.